Review Of Project Delay Factors On Project Cost Explanation : Lampung Sugar Factory – Mill House - Kusumawati, Jujuk; Silaban, Rolan Mediana (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
The problem of delays in the construction industry is a national phenomenon and Jakarta is no exception. The main purpose of this study is to identify the factors of project delays and their effects on cost overruns for building projects in Jakarta. ) contractor experience, (3) work methods (4) material delays, (5) tool mobilization (6) precast material fabrication (7) work quality (8) worker quality (9) field cashflow (10) subcontractors. Then an analytical survey was conducted which was distributed to 26 respondents. The ten delay factors were analyzed to determine their effect on project cost overruns. From the results of the analysis it can be seen that: (1) office overhead (2) contractor experience, (3) work methods (4) material delays, (5) tool mobilization (6) precast material fabrication (7) work quality (8) worker quality (9) field cashflow (10) Subcontractors have their respective weights of influence on project cost overruns